In silico characterization of IncX3 plasmids carrying blaOXA-181 in Enterobacterales - Yu, Zhijian; Zhang, Zhengrong; Shi, Lile; Hua, Shengni; Luan, Ting; Lin, Qiuping; Zheng, Zhixiong; Feng, Xiaosan; Liu, Mubiao; Li, Xiaobin (Frontiers in Cellular and Infection Microbiology, 2022)
Carbapenem-resistant Enterobacterales poses a global urgent antibiotic resistance threat because of its ability to transfer carbapenemase genes to other bacteria via horizontal gene transfer mediated by mobile genetic elements such as plasmids. Oxacillinase-181 (OXA-181) is one of the most common OXA-48-like carbapenemases, and OXA-181-producing Enterobacterales has been reported in many countries worldwide. However, systematic research concerning the overall picture of plasmids harboring blaOXA-181 in Enterobacterales is currently scarce. In this study, we aimed to determine the phylogeny and evolution of blaOXA-181-positive (gene encoding OXA-181) plasmids. To characterize the plasmids harboring blaOXA-181 in Enterobacterales, we identified 81 blaOXA-181-positive plasmids from 35,150 bacterial plasmids downloaded from the NCBI RefSeq database. Our results indicated that diverse plasmid types harbored blaOXA-181 but was predominantly carried by IncX3-type plasmids. We systematically compared the host strains, plasmid types, conjugative transfer regions, and genetic contexts of blaOXA-181 among the 66 blaOXA-181-positive IncX3 plasmids. We found that IncX3 plasmids harboring blaOXA-181 were mostly ColKP3-IncX3 hybrid plasmids with a length of 51 kb each and were mainly distributed in Escherichia coli and Klebsiella pneumoniae. Most of the IncX3 plasmids harboring blaOXA-181 were human origin. Almost all the blaOXA-181-positive IncX3 plasmids were found to carry genes coding for relaxases of the MOBP family and VirB-like type IV secretion system (T4SS) gene clusters, and all the 66 IncX3 plasmids were found to carry the genes encoding type IV coupling proteins (T4CPs) of the VirD4/TraG subfamily. Most IncX3 plasmids harbored both blaOXA-181 and qnrS1 in their genomes, and the two antibiotic resistance genes were found to a composite transposon bracketed by two copies of insertion sequence IS26 in the same orientation. Our findings provide important insights into the phylogeny and evolution of blaOXA-181-positive IncX3 plasmids and further address their role in acquiring and spreading blaOXA-181 genes in Enterobacterales.